Diffusion of point source pollution at the cross joint. Issue 1 (23rd December 2022) - Sun, Bin; Peng, Qingfeng; Ma, Wenjun; Li, Zhiwei; Song, Zhanqi; Tong, An
Abstract: The cross joint is one of the standard connection types for urban water supply pipelines. A pipeline containing cross joints was taken as the research object using NaCl as the tracer. The turbulent mixing characteristics of water and pollutants at the cross joints and pollutant migration and diffusion were studied and analysed by numerical analysis and experimental measurement. The primary purpose is to check the comprehensive influence of the six factors of pipe diameter, inlet flow ratio, outlet flow ratio, location of damage point, flow of brine, and density of brine on the turbulent mixing of water and brine in the pipeline. The coefficient of variation is used as an evaluation index to evaluate the mixing in the pipeline, and the effective mixing length L EML is used to quantify the uniform mixing position of brine in the pipeline. The results show that the inlet flow ratio, outlet flow ratio, and pipe diameter significantly affect L EML in the east outlet of the cross joint. Outlet flow ratio and pipe diameter significantly affect L EML in the cross joint's south outlet direction. In addition, the dimensionless relationship equation representing L EML is fitted through dimensional analysis. HIGHLIGHTS: The main and secondary factors affecting the pollutant diffusion at the cross joint were determined by orthogonal test. The influence of related factors on the turbulent mixing characteristics at the cross joint was studied by using the control variable method. The dimensionless equation representing the effective mixing length was fitted to quantify the mixing at the cross joint. Graphical Abstract